Measurement of Cooperative Accountability Implementation Based on Regulation of The Minister of Cooperatives and Small and Medium Enterprises of The Republic of Indonesia Number 20/Per/M.KUKM/IX/2015 (Case Study on YPTA Surabaya Employee Cooperative Period 2018-2021) - Joko Priyono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Cooperative accountability is one of the most important factors to be carried out by cooperative organizations so that they can be trusted by interested parties. This study was conducted to measure the implementation of cooperative accountability based on the Regulation of the Minister of Cooperatives and Small and Medium Enterprises Number 20/Per/M.KUKM/IX/2015 concerning the Implementation of Cooperative Accountability. The research site is the YPTA Surabaya Employee Cooperative for the 2018-2021 period. Aspects of measurement in this study include: measuring the implementation of organizational and management accountability; measurement of the implementation of cooperative service management accountability; and measuring the implementation of financial accountability. This research is descriptive research with a quantitative approach. The results of the research on measuring the implementation of cooperative accountability in the period 2018-2021 obtained fluctuating results. Measurement of organizational and management accountability; the number of members is decreasing but the number of deposits and institutional management are getting better. The measurement of the implementation of cooperative service management accountability on a gross basis to members and non-members has decreased while on a net basis it has increased. Measurement of the implementation of financial accountability; financial statements need to be audited by public accountants, the ability of cooperatives to fulfill all their obligations with their assets is very good; the ability of cooperatives to utilize assets on average is 1.3 times; and the ability to generate residual income tends to increase.